Enhancing the Quality and Adoption of Local Organic Fertilizer through a Farmer Assistance Program in Lumajang: Peningkatan Kualitas dan Pemanfaatan Pupuk Organik Lokal melalui Program Pendampingan Petani di Lumajang - Amin Silalahi; Karnadi Karnadi; Balthasar Watunglawar (Room of Civil Society Development, 2026)
This community service program aimed to strengthen the quality and competitiveness of local organic fertilizer in Lumajang through farmer assistance and educational activities. The main problem faced by P4S Asri Farm Kedungrejo was the high rate of farmers shifting to fertilizer products from Banyuwangi, which were considered more effective in increasing crop yields. The program involved 30 farmers from the assisted farmer group of P4S Asri Farm Kedungrejo. The activities were implemented using a participatory approach through five stages: initial survey, focus group discussion and SWOT analysis, training on improving the quality of locally based organic fertilizer production, assistance in packaging innovation and community-based promotion, and monitoring and evaluation. The results showed a 40% increase in farmers’ understanding of the advantages of local organic fertilizer based on pre-test and post-test results. Farmers’ confidence in local fertilizer also increased, followed by a rise in the use of local fertilizer from 35% to 55% within one planting season. The program also produced practical outputs, including a 30-page training module, improved product packaging, and the establishment of a farmer-based promotion team. These findings indicate that participatory and field-based assistance can strengthen farmers’ trust and encourage the gradual adoption of local organic fertilizer, thereby supporting agricultural sustainability and local farming resilience in Lumajang.